Uterine torsion in a case of previous two caesarean section mimicking uterine rupture: a case report - Agrawal, Priti; Agrawal, Rishi; Chandrakar, Jyotirmay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Uterine torsion (UT) is defines as a rotation of the uterus of more than 45 degree on its long axis. The predisposing factors for UT can be uterine asymmetry due to fibroids or mullerian anomalies, foetal malpresentation, pelvic adhesions and abdominal or ligamentous laxity other possible causes include external cephalic version, maternal trauma and abdominal massage. The clinical presentation of UT is non-specific. We report a case of previous 2 CS where we suspected rupture uterus but intraoperatively it was UT with unruptured fibrosed scar of previous CS. A 31 years old, G3P2 presented in emergency department with history of amenorrhea 9 months and severe abdominal pain for 5-6 hours. She had previous 2 CS done for contracted pelvis. We immediately suspected rupture of previous CS scar. On laparotomy dense intra-abdominal adhesions were found. After adhesiolysis we could find any sign of previous scar on the visible uterine wall. Entire uterine wall seemed as if we were doing CS in a primiparous patient. This made us suspicious of UT. UT is considered rare and has been referred to as an ‘obstetrician’s once in a lifetime diagnosis’. Recently cases have been reported with no associated pelvic factors although a common feature in all these cases had been previous CS. UT is a potentially dangerous complication of pregnancy both to the mother and to the foetus. Maternal mortality in modern era highly unexpected event but maternal morbidity can occur because of complications like uterine rupture, uterine abruptio, sepsis, pulmonary embolism and iatrogenic complications like injury to blood vessels, urinary tract and rectum. During laparotomy where correction of UT is not possible, a deliberate posterior hysterotomy can be done for delivery of foetus. Bilateral plication of the round ligaments can be done to prevent immediate postpartum recurrence of UT. UT though rare should be kept in mind while performing CS in cases of previous CS, associated myomas, ovarian tumour, malpresentations of foetus. Clinical symptoms may be absent or nonspecific and the diagnosis may be intraoperative.